2018
DOI: 10.1177/1941738118778510
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors for Sports Specialization and Injury in Youth Athletes

Abstract: As SES increases, young athletes report higher degrees of sports specialization, greater participation in individual sports, and more serious overuse injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 21 publications
1
38
1
Order By: Relevance
“…A previous study of 1544 high school athletes from various sports reported that 49% of all athletes also participate on a club team. Previous research estimating the prevalence of specialization has reported rates between 13% and 37%, with rates depending on a variety of factors including school size, athlete sex, age, sport, parent SES, and geographical region [10,19,[28][29][30][31]. The specific sport (baseball) examined, the affluence of our sample, and the differences in geographical region from previous research (Southern California vs primarily Midwest United States) most likely contributed to the increased rates of specialization and club sport participation observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of 1544 high school athletes from various sports reported that 49% of all athletes also participate on a club team. Previous research estimating the prevalence of specialization has reported rates between 13% and 37%, with rates depending on a variety of factors including school size, athlete sex, age, sport, parent SES, and geographical region [10,19,[28][29][30][31]. The specific sport (baseball) examined, the affluence of our sample, and the differences in geographical region from previous research (Southern California vs primarily Midwest United States) most likely contributed to the increased rates of specialization and club sport participation observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, individuals from low-income areas have reduced access to club sports. 45,46 The effects on mental and physical health we identified are complex and may be due to a combination of many factors that disproportionately affect individuals of low socioeconomic status. 47 It is still important to note that the cancellation of school sports may have a differential effect on the health of athletes depending on their level of poverty.…”
Section: Poverty Levelmentioning
confidence: 99%
“…Currently, the 3-question specialization survey that includes the question about quitting other sports is widely used as the method of stratifying specialization level in specialization research and literature. [2][3][4]14 Our findings suggest that researchers should consider modifying the commonly used sport-specialization survey to account for athletes who never played other sports. One possibility would be to add a fourth question, ''Have you only ever played 1 sport?''…”
Section: Discussionmentioning
confidence: 93%